Executive Function and Emotion Regulation Strategy Use in Adolescents. Issue 1 (2nd January 2016) - Lantrip, Crystal; Isquith, Peter K.; Koven, Nancy S.; Welsh, Kathleen; Roth, Robert M.
Abstract : Development of emotion regulation strategy use involves a transition from reliance on suppression during childhood to greater use of reappraisal in adolescence and adulthood—a transition that parallels developmental changes in executive functions. We evaluated the relationship between emotion regulation strategy use and executive functioning in the everyday life of 70 typically developing adolescents who completed the Emotion Regulation Questionnaire for Youth and the Behavior Rating Inventory of Executive Function-Self-Report. Results indicated that greater reliance on reappraisal was associated with better executive functions, while reliance on suppression was related to poorer executive functions. Findings suggest that adolescents who rely on reappraisal may have more cognitive resources to help them remain attentive and well regulated in their daily lives. On the other hand, if better executive functions facilitate the use of reappraisal, adolescents' ability to regulate their emotions could potentially be enhanced via supports for executive functions.